Penerapan E-Commerce Pada Penjualan Gula Tumbu Berbasis Web - Amirudin, Moh Faqih Amirudin; Listyorini , Tri Listyorini; Endang Supriyati (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2022)
Tumbu sugar is brown sugar made from sugar cane in a very traditional processing method. From the process from pressing to boiling in a cauldron, deposition and molding in a container called a tumbu, everything is done traditionally. The maker is located in the district of Dawe, Kudus Regency, in the modern era, marketing of products is still on a local and conventional scale. With the development of the era, the conventional buying and selling system is rarely less attractive to today's society, more towards online purchases, making transactions easy and practical. Because of that, an e-commerce system was made into an online media. Information and purchasing of goods can be faster & marketing reach is wider, consumers don't have to come to the store to make purchases. The data collection methods used in the study were interviews and direct observation. This system was created using the codeign-niter framework and the waterfall research method